(untitled) (REMUNOM, 2025)
Abstract The purpose of this article is to analyze the uniqueness of the memory dimension in hypochondriasis. The physical pain that characterizes him represents one of the most archaic ways of living the experience of death, projecting itself into the concreteness and immediacy of the body. In hypochondria, the persecutory character acting on the subject’s body represents a ’realization’ in the sense of a demonic reappearance of the original traumatic experience. The imminent danger of death resulting from the serious illness that these subjects believe they are suffering from represents a permanent awareness of their physical condition. This is attributed to the persistence of mental life during the time presented, which is the near-old age of the perceptual register. In this way, the ego realizes its most basic and primordial mode of existence and, paradoxically, protects itself from the effects of traumatic events. However Pharmaceutical assistance is an essential tool in treating patients with hypochondriasis because hypochondriasis is a complex disease that involves everything from dosing schedules to the use of medications that affect the central nervous system and the patient’s daily life. Keywords: Hypochondria. Pharmaceutical care. Imminent pain.